Switzerland : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
The Selected Issue Paper discusses the Swiss National Bank's (SNB) balance sheet risks and policy implications. Despite increased profit allocations, SNB capital has not kept pace with its growing balance sheet. The paper also explores the empirical determinants of pressures on the Swiss franc with the purpose of sorting out the relative importance of four factors: conventional monetary policy stance in other advanced countries and large emerging markets; quantitative easing and other unconventional policies pursued by major central banks; the euro area sovereign debt crisis; and global risk aversion.